A Bifunctional Saddle‐Shaped Small Molecule as a Dopant‐Free Hole Transporting Material and Interfacial Layer for Efficient and Stable Perovskite Solar Cells. Issue 5 (20th March 2019) - Lai, Xue; Meng, Fei; Zhang, Qian‐Qian; Wang, Kai; Li, Gongqiang; Wen, Yaping; Ma, Haibo; Li, Wenhui; Li, Xianqiang; Kyaw, Aung Ko Ko; Wang, Kai; Sun, Xiao Wei; et al.
Abstract : Herein, a new bifunctional saddle‐shaped organic small molecule named 2, 2′, 7, 7′‐tetrakis(N, N‐di‐p‐methoxyphenyl‐aniline)‐α, β‐cycloocta[1, 2‐b:4, 3‐b′:5, 6‐b′:8, 7‐b″′]tetrathiophenyl (α, β‐COTh‐Ph‐OMeTAD) is synthesized. When compared with spiro‐OMeTAD, a star hole transporting material (HTM) for highly efficient perovskite solar cells, the new material has a deeper highest occupied molecular orbital (HOMO) energy level of −5.30 eV, and a higher hole mobility of 2.88 × 10 −4  cm 2  V −1  s −1 . With dopant‐free α, β‐COTh‐Ph‐OMeTAD as a HTM and an interfacial layer combinined with chlorobenzene (CB) as the anti‐solvent, mesoporous perovskite solar cells (PSCs) are fabricated, which exhibit a power conversion efficiency (PCE) of 17.22% under AM 1.5 conditions, which is a little higher than that of devices based‐on doped spiro‐OMeTAD under the same conditions, which is 16.83%. Notably, the PSCs devices with dopant‐free α, β‐COTh‐Ph‐OMeTAD as both the HTM and interfacial layer show better stability, and after being stored in dark and dry air without encapsulation for nearly 800 h, the PCE can still be maintained at 86% of the maximum. This opens a new avenue for efficient and stable PSCs by exploring new dopant‐free materials as alternatives to spiro‐OMeTAD. Abstract : A bifunctional saddle ‐shaped small molecule α, β‐COTh‐Ph‐OMeTAD is synthesized and systemically charactered as a dopant‐free hole transporting material and interfacial layer in perovskite solar cells (PSCs). A higher power conversion efficiency (PCE) (17.22%) and stable‐enhanced PSCs devices are achieved when compared with that based on spiro‐OMeTAD (16.66%). Noteworthily, after storing nearly for 800 h, 86% of the maximum PCE is retained without any encapsulation.